Pemanfaatan Buah Salak untuk Meningkatkan Pendapatan dan Kepatuhan Pajak Final bagi Petani - Baharudin Saga; Yunus Nurhasan; Khuzaeni Khuzaeni; Rananda Septanta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The utilization of salak fruit has potential to increase farmers' income and improve compliance with final income tax obligations in Indonesia especially rural farmers in processing local agricultural commodities. This community service program aims to enhance knowledge and skills of participants regarding value-added salak processing and tax awareness and strengthening awareness of tax obligations among informal sector communities. Methods: The PKM activity was conducted at Yayasan Yatim dan Piatu Pamulang, South Tangerang, on April 11, 2026, involving five lecturers from Universitas Pamulang and 23 participants consisting of children and teachers as part of community empowerment program. Activities were implemented through presentation practical training group discussion and question-and-answer sessions following preparation implementation and reporting stages to improve understanding and participation in collaborative learning. Results showed increased understanding of salak-based product development improved awareness of income generation opportunities and enhanced understanding of final tax compliance among participants in supporting household economy of participants families through improved value addition practices. The program also strengthened engagement between lecturers and community members particularly children and teachers of the orphanage foundation and provided practical insights into small-scale entrepreneurship opportunities based on local resources approach.